Shared‐life communities for people with a learning disability: A review of the evidence. (7th May 2018) - Cumella, Stuart; Lyons, Maria
Abstract : Accessible Summary: This is about the best places to live for people with a learning disability. It compares ordinary houses with communities where people with a learning disability share the homes of people who are not disabled. These communities may be just as good a place to live as ordinary houses because there are interesting work and more friends. People with a learning disability should have a choice where they want to live. Abstract: Background: A key aim of public policy has been to move people with a learning disability from segregated settings into ordinary housing, with the expectation that they would become integrated in and accepted by the rest of society. Despite this policy, people with a learning disability have high rates of unemployment, social isolation, mental disorders and premature death. Aims: This raises questions about the dominant capitalist mode of care and makes it essential to consider alternative types of residence. Materials and Methods: This study reviews research into shared‐care communities in which people with a learning disability share their lives with families and volunteers ("co‐workers"), either in dispersed housing or in village settlements. Results: Reviews of research into types of accommodation for people with a learning disability have compared dispersed housing with "congregate" housing, finding that the former provide a better quality of life. However, they also found wide variations in outcome, which can be attributed to the heterogeneous range of accommodation categorised as "congregate." When shared‐care communities are analysed separately, they were found to offer accommodation as homely as dispersed housing, with a similar lack of institutional practices. Residents in shared‐care communities were also more likely than those in other types of accommodation to be involved in planning their own lives and in accessing professional health and social care. Research into shared‐care communities has attributed these outcomes to the availability of meaningful and diverse employment, opportunities for friendship and long‐term relationships with co‐workers. Discussion: These conclusions are supported by the results of official inspections and by recent research, which has emphasised how the quality of life of residents with a learning disability is improved when there are long‐term emotional bonds between staff and clients. It is concluded, therefore, that shared‐care communities offer a viable alternative to traditional dispersed housing for people with a learning disability. Choice of accommodation has often been denied to people with a learning disability, even though the rest of the population now live in a wide variety of living circumstances. It is therefore recommended that public policy accepts the need for shared‐life communities as one of a range of living options for people with a learning disability, rather than enforcing one type of accommodation deemed "normal.